Beyond Measure : Neglected Elements of Accountability. - Holland, Patricia (Taylor and Francis, 2013)
This book shows that the current focus on high stakes tests has narrowed the definition of a successful school. It demonstrates that, in addition to focusing on standardized measures, educators also need to look at other matters, such as what actually goes on in their classrooms, teachers' professional development, parental involvement, and school climate. These chapters were written by school leaders who are champions of accountability, but who also ask us to take a look at the "bigger picture."